2018
DOI: 10.1002/lio2.236
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between allergy and chronic rhinosinusitis

Abstract: Objective To summarize the current evidence regarding a relationship between chronic rhinosinusitis (CRS) and allergy. Methods Literature review. Results Despite frequent assumption of an association between CRS and allergy the relationship between these entities remains poorly defined. Certain CRS entities, however, have demonstrated a strong association with allergy—namely allergic fungal rhinosinusitis and central compartment atopic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…20,21 Yet, a major limitation in the literature is that all CRSwNP variants were often included within a single "CRSwNP cohort," despite evidence of a greater association of allergy with specific subtypes, including AFRS and CCAD. 9,10 In our analysis, overall allergy prevalence was high (78.7%), as determined by clinical history of AR in CRSwNP patients. However, when separated by subtype, allergy prevalence varied significantly across groups.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…20,21 Yet, a major limitation in the literature is that all CRSwNP variants were often included within a single "CRSwNP cohort," despite evidence of a greater association of allergy with specific subtypes, including AFRS and CCAD. 9,10 In our analysis, overall allergy prevalence was high (78.7%), as determined by clinical history of AR in CRSwNP patients. However, when separated by subtype, allergy prevalence varied significantly across groups.…”
Section: Discussionmentioning
confidence: 55%
“…However, recent systematic reviews have demonstrated an equivocal relationship between allergy and CRSwNP (aggregate level of evidence D) . Yet, a major limitation in the literature is that all CRSwNP variants were often included within a single “CRSwNP cohort,” despite evidence of a greater association of allergy with specific subtypes, including AFRS and CCAD . In our analysis, overall allergy prevalence was high (78.7%), as determined by clinical history of AR in CRSwNP patients.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The number of rhinosinusogenic orbital and intracranial complications, often leading to disability or death of the patient, has at least not decreased recently [16,17].…”
Section: Resultsmentioning
confidence: 99%